MALAYSIAN INTEGRATED 3D CADASTRE - Hassan, Muhammad Imzan (BHUMI: Jurnal Agraria dan Pertanahan, 2018)
This paper discusses 3D cadastre in the aspect of property registration i.e. complex building and overlapping properties on different land use. We also discuss the interoperability of the two systems between the two different agencies. This 3D cadastre registration will serve as a first attempt to develop a more complete Integrated Malaysian 3D Cadastre System. A complex system needs a clear and concise method to show the representation of data, and here we utilize Unified Modeling Language (UML) for the data modeling task as it has been considered better technique for such real world data modeling like cadastre data compared to the traditional entity relationship approach. Besides 3D registration, this paper also discusses 3D modeling, 3D geo databasing and 3D visualization. Malaysia could embark on this 3D cadastre system since it has well established 2D cadastre framework. From the previous research and discussion it can be realized that the hybrid approach certainly would be a good approach for Malaysian 3D Cadastre System. The hybrid approach means preservation of 2D cadastre and the integration of the registration of the situation in 3D by registering 3D situations integrated and being part of the 2D cadastral geographical data set. Keywords: 3D Cadastre, 3D Database